Composite laminated battery and preparation method thereof
By adopting a composite laminate structure in lithium-ion batteries, using the combination of single-particle graphite and secondary-particle graphite, the problem of difficulty in infiltration of electrolyte is solved, the battery is emulsive and cost-effective, and high energy density and long The effect of cycle life.
Patent Information
- Application Number
- CN202411202788.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-08-29
AI Technical Summary
Increased thickness and energy density of lithium-ion batteries lead to difficulty in infiltration of electrolytes. The existing high-temperature stand-alone and prolonged stand-alone process increases production costs and cannot effectively solve the problem.
The composite laminated structure is adopted, with single-particle graphite as the outer negative electrode sheet and secondary-particle graphite as the inner negative electrode sheet, and separated by a separator. The electrolyte is rapidly diffused by the high liquid absorption rate of single-particle graphite to shorten the wetting time.
It improves the wetting properties of the battery cell, reduces material costs, improves the simplicity of the battery production process, solves the infiltration difficulties caused by the increase in thickness and energy density of lithium-ion batteries, and improves the consistency of coating and cycle life.
Smart Images

Figure CN119133625A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a composite laminate battery and a preparation method thereof. Background Art
[0002] As a new type of secondary battery, lithium batteries have been continuously expanded in scope of application due to their advantages such as high energy density and long cycle life. They are widely used in portable electronic devices, energy storage and power vehicles. Especially with the rapid development of the new energy industry, lithium batteries are increasingly used in power vehicles. However, with the increase in thickness and energy density of lithium batteries, there is still a problem of electrolyte wetting difficulties in the preparation process. In response to the wetting problem, the battery wetting process currently widely used by lithium battery manufacturers is to use high-temperature standing conditions and extend the standing time. High-temperature standing will increase the production cost of lithium batteries, and extended standing time will reduce the efficiency of production line use, indirectly increase the cost of lithium batteries, and reduce product market competitiveness. Moreover, even if high-temperature standing and extended standing time are used, the wetting problem of high-energy-density battery systems cannot be solved.
[0003] In view of the difficulty of wetting caused by the increase in thickness and energy density of lithium batteries, the present invention is proposed. Summary of the invention
[0004] The purpose of the present invention is to provide a composite laminated battery and a preparation method thereof, mainly by setting the outer layer of the negative electrode plate of the laminated battery cell to be single-grain graphite and the inner layer to be secondary-grain graphite, so as to solve the technical problem of difficulty in wetting caused by increased thickness and improved energy density of lithium-ion batteries.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] In a first aspect, a composite laminated battery comprises a laminated battery cell comprising a first negative electrode sheet A selected from a single-particle graphite, a second negative electrode sheet B selected from a secondary-particle graphite, and a positive electrode sheet C, wherein the positive and negative electrode sheets in the laminated battery cell are stacked in an arrangement of A / C / A / C / A / C…A / C / B / C / B / C… / B / C / A / C…A / C / A and separated by a diaphragm, and the single-particle graphite and secondary-particle graphite have the same gram capacity.
[0007] Further, the D50 of the single graphite particle is 8-15 μm;
[0008] and / or, the D50 of the secondary graphite particles is 15-16 μm;
[0009] And / or, the gram capacity of the single graphite particle and the secondary graphite particle is 335-355 mAh / g.
[0010] Furthermore, the first negative electrode sheet A and the second negative electrode sheet B have the same compaction density, material mass ratio and surface density;
[0011] And / or, the number of the first negative electrode sheets A and the second negative electrode sheets B are respectively positive integers m and n, and the number of the positive electrode sheets C is m+n-1.
[0012] Furthermore, the compaction density of the first negative electrode sheet A and the second negative electrode sheet B are both 1.50-1.65 g / cm 3 ;
[0013] And / or, the mass ratio of the first negative electrode sheet A and the second negative electrode sheet B is 94-97:0.5-2:3.0-4.5 according to the calculation of negative electrode active material:conductive agent:binding agent;
[0014] And / or, the surface density of the first negative electrode sheet A and the second negative electrode sheet B are both 150-175 g / m 2 ;
[0015] And / or, the ratio of the number m of the first negative electrode sheets A to the number n of the second negative electrode sheets B is 1:4 to 1.5:1.
[0016] Furthermore, the compaction density of the first negative electrode sheet A and the second negative electrode sheet B are both 1.50-1.55 g / cm 3 , the ratio of the number m of the first negative electrode sheets A to the number n of the second negative electrode sheets B is 1:4 to 3:7;
[0017] And / or, the compaction density of the first negative electrode sheet A and the second negative electrode sheet B are both 1.55-1.65 g / cm 3 The ratio of the number m of the first negative electrode sheets A to the number n of the second negative electrode sheets B is 1:1 to 3:2.
[0018] Furthermore, the mass ratio of the ingredients of the positive electrode sheet C is 96-98:0.5-2.0:1.5-3.0 according to the positive electrode active material:conductive agent:binding agent;
[0019] And / or, the positive electrode active material of the positive electrode sheet C is lithium iron phosphate.
[0020] Furthermore, the diaphragm is a ceramic diaphragm coated with glue on one side.
[0021] Furthermore, the thickness of the laminated battery core is 25 to 35 mm.
[0022] Furthermore, the energy density of the battery is 165-175Wh / kg.
[0023] In a second aspect, a method for preparing the battery described in the first aspect comprises the steps of batching, coating, rolling, die-cutting, lamination, baking, liquid injection, formation, and capacity separation, wherein, during batching, single-particle graphite is prepared in the slurry of the first negative electrode sheet A, and secondary-particle graphite is prepared in the slurry of the second negative electrode sheet B, and the single-particle graphite and secondary-particle graphite have the same gram capacity; during lamination, the first negative electrode sheet A, the second negative electrode sheet B, and the positive electrode sheet C are stacked in the arrangement of A / C / A / C / A / C…A / C / B / C / B / C… / B / C / A / C…A / C / A and separated by a diaphragm.
[0024] Compared with the prior art, the present invention mainly discloses a new type of composite laminated battery and its preparation method, which not only simplifies the manufacturing process of the battery, but also improves the wettability of the battery cell and reduces the material cost to a certain extent. It has at least the following beneficial effects:
[0025] 1. The present invention adopts a composite lamination form of A / C / A / C / A / C…A / C / B / C / B / C… / B / C / A / C…A / C / A. Compared with the traditional single negative electrode B / C / B / C… / B / C lamination form, it has an additional single-particle graphite negative electrode A, which not only has the high capacity and rate advantages of secondary particles, but also has the characteristics of single-particle structural stability and long cycle life. And under the condition of using the same coating surface density and compaction density, the liquid absorption rate of the pole piece of single-particle graphite is faster than that of the pole piece of secondary particle graphite. The single-particle graphite negative electrode sheet is placed in the outer layer of the core stack, and the secondary particle graphite negative electrode sheet is placed in the inner layer. With the pole piece with fast liquid absorption in the outer layer, the electrolyte can quickly diffuse to the inner layer, shortening the electrolyte infiltration time, solving the problem of difficulty in infiltration caused by increased thickness and increased energy density of lithium-ion batteries.
[0026] 2. Compared with graphite mixed with single particles and secondary particles, it reduces the uneven mixing of slurry and can improve the consistency of coating.
[0027] 3. Under the same raw materials, single-grain graphite has fewer granulation steps than secondary-grain graphite, which has certain advantages in production cost. In addition, the use of single-grain graphite also reduces the use of secondary-grain graphite, which reduces material costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0029] Figure 1A schematic diagram of the battery stacking method of the present invention;
[0030] Figure 2 1.52 g / cm at 45°C 3 Liquid absorption graph of compacted core stack;
[0031] Figure 3 1.60g / cm at 45℃ 3 Liquid absorption graph of compacted core stack;
[0032] Figure 4 1.52g / cm 3 The rate charge capacity retention diagram of the compacted core stack;
[0033] Figure 5 1.52g / cm 3 The rate discharge capacity retention diagram of the compacted core stack;
[0034] Figure 6 1.60g / cm 3 The rate charge capacity retention diagram of the compacted core stack;
[0035] Figure 7 1.60g / cm 3 The rate discharge capacity retention rate diagram of the compacted core stack. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.
[0037] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.
[0038] In view of the difficulty of wetting caused by the increase in thickness and energy density of lithium batteries, this patent invents a composite laminated battery and its preparation method. The details are as follows:
[0039] A composite laminated battery comprises a laminated battery cell comprising a first negative electrode sheet A selected from a single-grain graphite particle, a second negative electrode sheet B selected from a secondary-grain graphite particle, and a positive electrode sheet C. The positive and negative electrode sheets in the laminated battery cell are laminated in an arrangement of A / C / A / C / A / C...A / C / B / C / B / C... / B / C / A / C...A / C / A and separated by a diaphragm. The single-grain graphite particle and the secondary-grain graphite particle have the same gram capacity.
[0040] The conventional stacking process battery all uses a single negative electrode sheet A or B and a positive electrode sheet C, in the form of A / C / A / C...A / C or B / C / B / C...B / C, the positive and negative electrode sheets are separated by a diaphragm, and the stacking is performed to obtain a stacked core. However, in the battery of the present invention, two kinds of electrode sheets are selected for the negative electrode, and under the condition that the negative electrode ratio and surface density are the same and the same excess ratio (excess ratio = negative electrode gram capacity × active material ratio × coating surface density / (positive electrode gram capacity × active material ratio × coating surface density)) and rolling thickness are ensured, one negative electrode sheet active material uses a single-grain graphite, and the other negative electrode sheet active material uses a secondary-grain graphite, the gram capacity of the secondary particles is the same as that of the single particles, and the ingredients are prepared according to the same ratio, coated, rolled and die-cut to obtain a first negative electrode sheet A (abbreviated as A) using a single-grain graphite and a second negative electrode sheet B (abbreviated as B) using a secondary-grain graphite; the positive electrode is obtained according to the normal manufacturing process to obtain a positive electrode sheet C (abbreviated as C). The positive and negative electrode sheets are stacked in the arrangement of A / C / A / C / A / C...A / C / B / C / B / C... / B / C / A / C...A / C / A, and the positive and negative electrode sheets are separated by a separator to obtain the final stacked battery cell (referred to as stacked core), where the number of A and B in the negative electrode sheets are positive integers m and n respectively, and the number of positive electrode sheets is m+n-1. The stacked core is then baked, injected, and other processes to obtain the off-line battery.
[0041] The present invention adopts the form of composite lamination, which is more than the traditional single lamination form of B / C / B / C... / B / C. First, there is an additional single-particle graphite negative electrode sheet, which not only has the high capacity and rate advantages of secondary particles, but also has the characteristics of single-particle structural stability and long cycle life. And under the condition of using the same coating surface density and compaction density, the liquid absorption rate of the pole piece of single-particle graphite is faster than that of the pole piece of secondary particle graphite. The single-particle graphite negative electrode sheet is placed in the outer layer of the core stack, and the secondary particle graphite negative electrode sheet is placed in the inner layer. With the pole piece with fast liquid absorption in the outer layer, the electrolyte can quickly diffuse to the inner layer, shortening the electrolyte infiltration time, and solving the problem of difficulty in infiltration caused by increased thickness and increased energy density of lithium-ion batteries. Second, compared with the graphite mixed with single particles and secondary particles as a negative electrode active material, the uneven mixing of the slurry is reduced, and the consistency of coating can be improved. Third, under the same raw materials, single-particle graphite has less granulation process than secondary particle graphite, which has certain advantages in production cost. In addition, the use of single particles also reduces the use of secondary particles, thereby reducing material costs.
[0042] In the present invention, single-grain graphite, i.e., primary-grain graphite, refers to primary particles prepared from raw materials through multiple steps such as crushing, graphitization, and screening; and secondary-grain graphite refers to the ultimate particles made by subjecting primary-grain graphite to a granulation process. For example, secondary particles are generally formed by adding asphalt as a binder and bonding primary particles into agglomerates at high temperatures to form secondary particles.
[0043] As an optional embodiment of the battery of the present invention, the D50 of the single graphite particle is 8-15 μm;
[0044] and / or, the D50 of the secondary graphite particles is 15-16 μm;
[0045] And / or, the gram capacity of the single graphite particle and the secondary graphite particle is 335-355 mAh / g.
[0046] The graphite used in the battery of the present invention can be the product of BTR New Materials Group Co., Ltd. (BTR), Shanshan New Energy Co., Ltd. (Shanshan) or Xiangfenghua New Energy Materials Co., Ltd. (Xiangfenghua). Specifically, the single-particle graphite can be the product of BTR or Shanshan, with D50 of 8-12 μm, no carbon coating, and compacted at 1.55 g / cm 3 The gram capacity is about 340mAh / g. The secondary particle graphite is also made of Shanshan or BTR materials, with a D50 of 15-16μm, no carbon coating, and compacted at 1.55g / cm 3 Or, the single particle adopts the products of BTR, Shanshan or Xiangfenghua, with D50 of 9-14μm, no carbon coating, and compaction of 1.65g / cm 3The gram capacity is about 350mAh / g. The secondary particles are also made of Shanshan, B&T or Xiangfenghua materials, with a D50 of 15-16μm, no carbon coating, and compacted at 1.65g / cm 3 The gram capacity is about 350 mAh / g. Optionally, the D50 of the single-grain graphite can be typically but not limited to 8.5 μm, 9 μm, 9.5 μm, 10 μm, 10.5 μm, 11 μm, 11.5 μm, 12 μm, 12.5 μm, 13 μm, 13.5 μm, 14 μm, 14.5 μm, etc.; the D50 of the secondary-grain graphite can be typically but not limited to 15.1 μm, 15.2 μm, 15.3 μm, 15.4 μm, 15.6 μm, 15.7 μm, 15.8 μm, 15.9 μm, 15.10 μm, 15.11 μm, 15.12 μm, 15.13 μm, 15.14 μm, 15.15 μm, 15.16 μm, 15.17 μm, 15.18 μm, 15.19 μm, 15.20 μm, 15.21 μm, 15.22 μm, 15.23 μm, 15.24 μm, 15.25 μm, 15.26 μm, 15.27 μm, 15.28 μm, 15.29 μm, 15.2 5μm, 15.6μm, 15.7μm, 15.8μm, 15.9μm, etc.; the gram capacity of single particle graphite and secondary particle graphite can be typically but not limited to 336mAh / g, 338mAh / g, 340mAh / g, 342mAh / g, 344mAh / g, 346mAh / g, 348mAh / g, 350mAh / g, 352mAh / g, 354mAh / g, etc.
[0047] As an optional embodiment of the battery of the present invention, the compaction density of the first negative electrode sheet A and the second negative electrode sheet B are both 1.50-1.65 g / cm 3 (e.g. 1.51 g / cm 3 、1.53g / cm 3 , 1.55g / cm 3 , 1.57g / cm 3 , 1.59g / cm 3 , 1.61g / cm 3 、1.63g / cm 3 wait);
[0048] And / or, the mass ratio of the first negative electrode sheet A and the second negative electrode sheet B is 94-97:0.5-2:3.0-4.5 (such as 94:2:4, 94.5:1.6:3.9, 95:1.3:3.7, 95.5:1:3.5, 96:0.7:3.3, 96.5:0.5:3, etc.) according to the calculation of negative electrode active material: conductive agent: binder;
[0049] And / or, the surface density of the first negative electrode sheet A and the second negative electrode sheet B are both 150-175 g / m 2 (such as 155g / cm 3 , 160g / cm 3 , 165g / cm 3 , 170g / cm 3 、174g / cm 3 wait);
[0050] And / or, the ratio of the number m of the first negative electrode sheets A to the number n of the second negative electrode sheets B is 1:4 to 1.5:1 (such as 1:3.8, 1.5:3.5, 2:3, 2.5:2.5, 3:2.1, etc.).
[0051] In the present invention, the negative electrode active material refers to single-particle graphite or secondary-particle graphite.
[0052] Furthermore, when the negative electrode sheet is compacted to 1.50-1.55 g / cm 3 The ratio of single particle to secondary particle number in the electrode can be selected from 1:4 to 3:7 (such as 2:7, 9:28, 5:14, 11:28, etc.); when the negative electrode is compacted to 1.55-1.65g / cm 3 For a single-particle negative electrode, the ratio of the number of single-particle and secondary-particle electrodes can be selected from 1:1 to 3:2 (such as 2.1:2, 2.3:2, 2.5:2, 2.7:2, 2.9:2, etc.).
[0053] In the present invention, there is no particular limitation on the binder and the conductive agent in the positive and negative electrode materials and the positive electrode active material in the positive electrode material, and existing conventional materials can be used, such as those commonly used in existing lithium batteries: the positive electrode active materials / materials include lithium iron phosphate, etc., the binders include PVDF (polyvinylidene fluoride), CMC (sodium carboxymethyl cellulose) and SBR (styrene-butadiene rubber), etc., the conductive agents include SP (carbon black), graphene, carbon nanotubes and VGCF (nanocarbon fibers), etc.
[0054] As an optional embodiment of the battery of the present invention, the mass ratio of the ingredients of the positive electrode sheet C is 96-98:0.5-2.0:1.5-3.0 (such as 96:1:3, 96.5:1.1:2.4, 97:1.2:1.8, 97.2:1.3:1.5, etc.) according to the positive electrode active material: conductive agent: binder;
[0055] And / or, the positive electrode active material of the positive electrode sheet C is lithium iron phosphate.
[0056] As an optional embodiment of the battery of the present invention, the diaphragm is a single-sided glue-coated ceramic diaphragm.
[0057] As an optional embodiment of the battery of the present invention, the thickness of the laminated battery core is 25 to 35 mm (such as 26 mm, 28 mm, 30 mm, 32 mm, 34 mm, etc.).
[0058] As an optional embodiment of the battery of the present invention, the energy density of the battery is 165-175Wh / kg (such as 166Wh / kg, 168Wh / kg, 170Wh / kg, 172Wh / kg, 174Wh / kg, etc.).
[0059] A preparation method of the battery comprises the steps of batching, coating, rolling, die-cutting, lamination, baking, liquid injection, formation and capacity separation, wherein, during batching, single-grain graphite is prepared in the slurry of the first negative electrode sheet A, and secondary-grain graphite is prepared in the slurry of the second negative electrode sheet B, and the single-grain graphite and secondary-grain graphite have the same gram capacity; during lamination, the first negative electrode sheet A, the second negative electrode sheet B and the positive electrode sheet C are stacked in the arrangement of A / C / A / C / A / C...A / C / B / C / B / C... / B / C / A / C...A / C / A and separated by a diaphragm.
[0060] The present invention will be further described below with reference to specific embodiments and comparative examples.
[0061] Example 1
[0062] A composite laminated battery, comprising a laminated battery core made of a first negative electrode sheet A of single-grain graphite, a second negative electrode sheet B of secondary-grain graphite, and a positive electrode sheet C, wherein the positive and negative electrode sheets in the laminated battery core are laminated in an arrangement of A / C / A / C / A / C...A / C / B / C / B / C... / B / C / A / C...A / C / A and separated by a diaphragm, and the specific lamination method is as follows Figure 1 As shown in the figure, the gram capacity of single-grain graphite and secondary-grain graphite is the same, both 340 mAh / g; the D50 of single-grain graphite is 8-12 μm, without carbon coating, and the compacted density is 1.55 g / cm 3 The D50 of secondary graphite particles is 15-16 μm, without carbon coating, and the compacted density is 1.55 g / cm 3 Both single-grain graphite and secondary-grain graphite are products of Shanshan New Energy Company.
[0063] The compaction density of the first negative electrode sheet A and the second negative electrode sheet B is 1.52 g / cm 3 , the pole piece surface density is 150~175g / m 2 ; The number of the first negative electrode sheet A and the second negative electrode sheet B are set according to the ratio of A:B=m:n=3:7, which are 21 pcs and 49 pcs respectively, and the number of the positive electrode sheet C is 69 pcs;
[0064] The mass ratio of the first negative electrode sheet A and the second negative electrode sheet B is 95.6:1:3.4 according to the calculation of negative electrode active material: conductive agent: binder; wherein the binder is CMC:SBR=1.4:2, and the conductive agent is SP;
[0065] The mass ratio of the ingredients of the positive electrode sheet C is 97.5:1:1.5 according to the calculation of positive electrode active material: conductive agent: binder; wherein the positive electrode active material is lithium iron phosphate, the binder is PVDF, and the conductive agent is SP;
[0066] The diaphragm adopts single-sided glue-coated ceramic diaphragm;
[0067] In the battery of this embodiment, the thickness of the laminated cell is 30 mm, and the energy density of the battery is 165-175 Wh / kg.
[0068] The preparation method of the above-mentioned battery includes the steps of batching, coating, rolling, die-cutting, lamination, baking, liquid injection, formation, and volume separation. During batching, single-grain graphite is prepared in the slurry of the first negative electrode sheet A, and secondary-grain graphite is prepared in the slurry of the second negative electrode sheet B. Specifically, the positive electrode is prepared according to lithium iron phosphate: SP: PVDF = 97.5: 1: 1.5, and the negative electrode is prepared according to single-grain / secondary-grain graphite: SP: CMC: SBR = 95.6: 1: 1.4: 2, and the slurry is prepared, and then coated and rolled.
[0069] Coating roller pressing: Control the surface density of the positive electrode sheet C to 300-360g / m 2 , compacted density is 2.40~2.45g / cm 3 The surface density of the first negative electrode sheet A and the second negative electrode sheet B are both 150-175 g / m 2 , compacted density is 1.52g / cm 3 ;
[0070] When stacking, as shown in the figure Figure 1 The arrangement sequence shown is A / C / A / C / A / C...A / C / B / C / B / C... / B / C / A / C...A / C / A and is separated by a diaphragm, and the diaphragm is a single-sided glue-coated ceramic diaphragm;
[0071] After the final baking, the moisture content is qualified and the battery is filled with liquid. After the filling, it is placed at 45℃ for 12-24 hours for formation. After formation, it is aged for 12-48 hours, divided into different capacities, and the battery is taken off the production line for performance testing.
[0072] Example 2
[0073] A composite laminated battery, comprising a laminated battery core made of a first negative electrode sheet A of single-grain graphite, a second negative electrode sheet B of secondary-grain graphite, and a positive electrode sheet C, wherein the positive and negative electrode sheets in the laminated battery core are laminated in an arrangement of A / C / A / C / A / C...A / C / B / C / B / C... / B / C / A / C...A / C / A and separated by a diaphragm, and the specific lamination method is as follows Figure 1 As shown. Among them, the gram capacity of single-grain graphite and secondary-grain graphite is the same, both 350mAh / g; the D50 of single-grain graphite is 9-14μm, without carbon coating, and the compacted density is 1.65g / cm 3 The D50 of secondary graphite particles is 15-16 μm, without carbon coating, and the compacted density is 1.65 g / cm 3 The single-grain graphite is a product of BTR New Materials Group Co., Ltd., and the secondary-grain graphite is a product of Xiangfenghua New Energy Materials Co., Ltd.
[0074] The compaction density of the first negative electrode sheet A and the second negative electrode sheet B is 1.60 g / cm 3 , the surface density of the pole piece is 180~200g / m 2 ; The number of the first negative electrode sheet A and the second negative electrode sheet B are set according to the ratio of A:B=m:n=1:1, which are 32 pcs and 32 pcs respectively, and the number of the positive electrode sheet C is 63 pcs;
[0075] The mass ratio of the first negative electrode sheet A and the second negative electrode sheet B is 95.6:1:3.4 according to the calculation of negative electrode active material: conductive agent: binder; wherein the binder is CMC:SBR=1.4:2, and the conductive agent is SP;
[0076] The mass ratio of the ingredients of the positive electrode sheet C is 97.5:1:1.5 according to the calculation of positive electrode active material: conductive agent: binder; wherein the positive electrode active material is lithium iron phosphate, the binder is PVDF, and the conductive agent is SP;
[0077] The diaphragm adopts single-sided glue-coated ceramic diaphragm;
[0078] In the battery of this embodiment, the thickness of the laminated battery core is 30 mm, and the energy density of the battery is 165-175 Wh / kg.
[0079] The preparation method of the above-mentioned battery includes the steps of batching, coating, rolling, die-cutting, lamination, baking, liquid injection, formation, and volume separation. During batching, single-grain graphite is prepared in the slurry of the first negative electrode sheet A, and secondary-grain graphite is prepared in the slurry of the second negative electrode sheet B. Specifically, the positive electrode is prepared according to lithium iron phosphate: SP: PVDF = 97.5: 1: 1.5, and the negative electrode is prepared according to single-grain / secondary-grain graphite: SP: CMC: SBR = 95.6: 1: 1.4: 2, and the slurry is prepared, and then coated and rolled.
[0080] Coating roller pressing: Control the surface density of the positive electrode sheet C to 350-400g / m 2 , compacted density is 2.45~2.55g / cm 3 The surface density of the first negative electrode sheet A and the second negative electrode sheet B are both 180-200 g / m 2 , compacted density is 1.60g / cm 3 ;
[0081] When stacking, as shown in the figure Figure 1 The arrangement order shown is A / C / A / C / A / C...A / C / B / C / B / C... / B / C / A / C...A / C / A and is separated by a diaphragm. The diaphragm is a single-sided glue-coated ceramic diaphragm.
[0082] After the final baking, the moisture content is qualified and the battery is filled with liquid. After the filling, it is placed at 45℃ for 24-36 hours for formation. After formation, it is aged for 12-48 hours, divided into different capacities, and the battery is taken off the production line for performance testing.
[0083] Comparative Example 1
[0084] A conventional laminated battery and a preparation method thereof, the difference from Example 1 is that there is only a first negative electrode sheet A, and the number of the first negative electrode sheets A is 70 pcs, that is, the positive and negative electrode sheets in the laminated battery cell are laminated in the arrangement of A / C / A / C / A / C...A / C / A. The rest of the settings are the same as Example 1.
[0085] Comparative Example 2
[0086] A conventional laminated battery and a preparation method thereof, the difference from Example 1 is that there is only a second negative electrode sheet B, and the number of the second negative electrode sheets B is 70 pcs, that is, the positive and negative electrode sheets in the laminated battery cell are laminated in the arrangement of B / C / B / C / B / C...B / C / B. The rest of the settings are the same as Example 1.
[0087] Comparative Example 3
[0088] A composite laminated battery and a preparation method thereof, the only difference from Example 1 is that the lamination positions of the first negative electrode sheet A and the second negative electrode sheet B are opposite to those of Example 1, that is, the positive and negative electrode sheets in the laminated battery cell are laminated in the arrangement of B / C / B / C / B / C...B / C / A / C / A / C / ...A / C / B / C...B / C / B, that is, the first negative electrode sheet A is in the inner layer of the laminated battery cell, and the second negative electrode sheet B is in the outer layer of the laminated battery cell. The rest of the settings are the same as those in Example 1.
[0089] Comparative Example 4
[0090] A conventional laminated battery and a preparation method thereof, the difference from Example 2 is that there is only a first negative electrode sheet A, and the number of the first negative electrode sheets A is 64 pcs, that is, the positive and negative electrode sheets in the laminated battery cell are laminated in the arrangement of A / C / A / C / A / C...A / C / A. The rest of the settings are the same as Example 2.
[0091] Comparative Example 5
[0092] A conventional laminated battery and a preparation method thereof, the difference from Example 2 is that there is only a second negative electrode sheet B, and the number of the second negative electrode sheets B is 64 pcs, that is, the positive and negative electrode sheets in the laminated battery cell are laminated in the arrangement of B / C / B / C / B / C...B / C / B. The rest of the settings are the same as Example 2.
[0093] Comparative Example 6
[0094] A composite laminated battery and a preparation method thereof, the only difference from Example 2 is that the lamination positions of the first negative electrode sheet A and the second negative electrode sheet B are opposite to those of Example 2, that is, the positive and negative electrode sheets in the laminated battery cell are laminated in the arrangement of B / C / B / C / B / C...B / C / A / C / A / C / ...A / C / B / C...B / C / B, that is, the first negative electrode sheet A is in the inner layer of the laminated battery cell, and the second negative electrode sheet B is in the outer layer of the laminated battery cell. The rest of the settings are the same as those of Example 2.
[0095] Testing and result analysis
[0096] The batteries obtained in Examples 1, 2 and Comparative Examples 1-6 were tested as follows:
[0097] 1. Wetting test
[0098] The liquid absorption rate can be characterized by immersing electrodes of the same weight in an equal amount of electrolyte, weighing the electrodes after the same time, and calculating the weight difference to characterize the amount of liquid absorbed.
[0099] When injecting the electrolyte, the same amount of electrolyte was injected into the embodiments of the present invention and the comparative examples, and the weight of the stacked core was measured after immersion for 24 hours, and the weight difference with that before immersion was calculated.
[0100] Figure 2 , 3 The liquid absorption of the stacked core under two kinds of compaction can be seen. It can be seen that the liquid absorption of the secondary particle graphite negative electrode sheet is lower than that of the single particle graphite negative electrode sheet, while the liquid absorption time is equal. It can be seen that the liquid absorption rate of the single particle graphite negative electrode sheet is higher, and it is introduced into the secondary particle graphite negative electrode sheet battery to form a composite stacking structure in which the single particle graphite negative electrode sheet is in the outer layer of the stacked battery core and the secondary particle graphite negative electrode sheet is in the inner layer of the stacked battery core. This better improves the liquid absorption rate of the secondary particle graphite negative electrode sheet battery, can better shorten the electrolyte infiltration time, and improve its infiltration difficulty. When the battery is compacted at 1.52g / cm 3 Under compaction, adding a small amount of single-grain graphite negative electrode sheets, that is, single-grain graphite negative electrode sheets account for 30% of the total number of negative electrode sheets, can increase the liquid absorption of the battery cell by 5% (calculated based on (mixed A outside - secondary particles B) / secondary particles B × 100%); when compacted at 1.60g / cm 3 When the single particle addition amount is 50%, the improvement is only 1.5% (calculated based on (mixed A outside - secondary particles B) / secondary particles B×100%).
[0101] 2. Rate charge and discharge test
[0102] The rate charge test is to charge to 3.65V at 0.33C / 0.5C / 1C / 2C constant current, and discharge to 2.5V at 0.33C constant current. The rate charge test results of the stacked core under different compaction are shown in Tables 1 and 2:
[0103] Table 11.52g / cm 3 Table of rate charging capacity retention rate of compacted core stack
[0104]
[0105] Table 21.60g / cm 3 Table of rate charging capacity retention rate of compacted core stack
[0106]
[0107] The rate discharge test is to discharge to 2.5V at 0.33C / 0.5C / 1C / 2C constant current, and charge to 3.65V at 0.33C constant current, with a constant voltage cut-off current of 0.05C. The rate discharge test results of the stacked cores under different compaction are shown in Tables 3 and 4:
[0108] Table 31.52g / cm 3 Table of rate discharge capacity retention of compacted core stack
[0109]
[0110] Table 41.60g / cm 3 Table of rate discharge capacity retention of compacted core stack
[0111]
[0112]
[0113] Table 1, Table 3, Figure 4 , 5 1.52g / cm 3 From the rate charge and discharge capacity retention rate of the compacted core, it can be seen that when charging does not exceed 1C, the rate charging performance of the single particle-on-the-outer composite laminate group of Example 1 is equivalent to that of Comparative Examples 2 and 3, but better than that of Comparative Example 1. However, when charging at 2C, the rate charging performance of the single particle-on-the-outer composite laminate group of Example 1 becomes inferior to that of Comparative Examples 2 and 3, but still better than that of Comparative Example 1. As for the discharge performance, the high-rate discharge capacity retention rate of the single particle-on-the-outer composite laminate group of Example 1 is equivalent to or even slightly better than that of the secondary particle group of Comparative Example 2, and is slightly higher than that of the other two groups.
[0114] Table 2, Table 4, Figure 6 , 7 1.60g / cm 3 From the rate charge and discharge capacity retention rate of each group under compaction, it can be seen that the rate charging performance of the single particle external composite stacking group of Example 2 is better than that of the other three groups; and the high-rate discharge capacity retention rate of the composite stacking group of Example 2 is equivalent to that of the secondary particle group of Comparative Example 5, which is higher than that of the single particle group of Comparative Example 4.
[0115] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A composite laminate battery, characterized in that: The invention comprises a laminated battery cell comprising a first negative electrode sheet A of a single-grain graphite, a second negative electrode sheet B of a secondary-grain graphite, and a positive electrode sheet C. The positive and negative electrode sheets in the laminated battery cell are stacked in an arrangement of A / C / A / C / A / C...A / C / B / C / B / C... / B / C / A / C...A / C / A and separated by a diaphragm. The single-grain graphite and the secondary-grain graphite have the same gram capacity.
2. The battery according to claim 1, characterized in that: The D50 of the single graphite particle is 8-15 μm; and / or, the D50 of the secondary graphite particles is 15-16 μm; And / or, the gram capacity of the single graphite particle and the secondary graphite particle is 335-355 mAh / g.
3. The battery according to claim 1, characterized in that: The first negative electrode sheet A and the second negative electrode sheet B have the same compaction density, material mass ratio and surface density; And / or, the number of the first negative electrode sheets A and the second negative electrode sheets B are respectively positive integers m and n, and the number of the positive electrode sheets C is m+n-1.
4. The battery according to claim 3, characterized in that: The compaction density of the first negative electrode sheet A and the second negative electrode sheet B are both 1.50-1.65 g / cm 3 ; And / or, the mass ratio of the first negative electrode sheet A and the second negative electrode sheet B is 94-97:0.5-2:3.0-4.5 according to the calculation of negative electrode active material:conductive agent:binding agent; And / or, the surface density of the first negative electrode sheet A and the second negative electrode sheet B are both 150-175 g / m 2 ; And / or, the ratio of the number m of the first negative electrode sheets A to the number n of the second negative electrode sheets B is 1:4 to 1.5:
1.
5. The battery according to claim 4, characterized in that: The compaction density of the first negative electrode sheet A and the second negative electrode sheet B are both 1.50-1.55 g / cm 3 , the ratio of the number m of the first negative electrode sheets A to the number n of the second negative electrode sheets B is 1:4 to 3:7; And / or, the compaction density of the first negative electrode sheet A and the second negative electrode sheet B are both 1.55-1.65 g / cm 3 The ratio of the number m of the first negative electrode sheets A to the number n of the second negative electrode sheets B is 1:1 to 3:
2.
6. The battery according to claim 1, characterized in that: The mass ratio of the positive electrode sheet C is 96-98:0.5-2.0:1.5-3.0 according to the positive electrode active material:conductive agent:binding agent; And / or, the positive electrode active material of the positive electrode sheet C is lithium iron phosphate.
7. The battery according to claim 1, characterized in that: The diaphragm is a single-sided glue-coated ceramic diaphragm.
8. The battery according to claim 1, characterized in that: The thickness of the laminated battery core is 25 to 35 mm.
9. The battery according to claim 1, characterized in that: The energy density of the battery is 165-175Wh / kg.
10. The method for preparing a battery according to any one of claims 1 to 9, characterized in that: The invention comprises the steps of batching, coating, rolling, die-cutting, lamination, baking, liquid injection, formation and volume separation, wherein, during batching, single-grain graphite is prepared in the slurry of the first negative electrode sheet A, and secondary-grain graphite is prepared in the slurry of the second negative electrode sheet B, and the single-grain graphite and secondary-grain graphite have the same gram capacity; during lamination, the first negative electrode sheet A, the second negative electrode sheet B and the positive electrode sheet C are stacked in the arrangement of A / C / A / C / A / C…A / C / B / C / B / C… / B / C / A / C…A / C / A and separated by a diaphragm.
